Comparison of two main orthokeratology lens designs in effectiveness and safety for myopia control in different ages - Li, Daoyuan; Yang, Qu; He, Mengting; Yang, Yinmao; Liu, Min; Ou, Shangkun (Frontiers in Medicine, 2025)
PurposeMyopia represents the most prevalent ocular condition among children and adolescents worldwide, exhibiting marked variations in prevalence across regions and ethnic groups. This study aimed to assess and compare the effectiveness and safety of two orthokeratology (OK) lens types—corneal refractive therapy (CRT) and vision shaping treatment (VST)—for controlling myopia progression across different age groups.MethodsA retrospective cohort analysis was performed on 105 pediatric patients (210 eyes; aged 8–16 years) clinically diagnosed with myopia who wore CRT or VST lenses for at least 12 months. Longitudinal evaluations included axial length (AL) progression, axial length-to-corneal curvature (AL/CR) ratio, corneal curvature, corneal eccentricity indices (e-values), and safety parameters.ResultsCRT lenses markedly limited AL elongation and reduced corneal curvature flattening in participants younger than 13 years (p < 0.0001), whereas VST lenses produced more favorable changes in E-values among those older than 11 years (p < 0.05). No significant difference was observed between the groups in the AL/CR ratio control (p > 0.05). Both lens designs maintained similar safety outcomes, with only mild corneal epithelial staining detected across all groups.ConclusionThe results reveal age-dependent variations in effectiveness, supporting an individualized approach to OK lens selection for optimized myopia management.